The integration of the Canadian Productivity Accounts within the System of National Accounts current status and challenges ahead - Baldwin, John R. 1945-; Harchaoui, Tarek M. (National Bureau of Economic Research, 2005)
"A statistical agency faces several challenges in building Productivity Accounts. What started out as a request for simple ratios of output to employment has moved to a demand for multifactor (total factor) productivity measures that take into account both labor and capital inputs, the compositional changes in both, and price corrections for the changing quality of outputs. The challenge that faces users of productivity measures is that many series often exist within statistical agencies that can be used on an ad hoc basis by outsiders to generate productivity estimates; however, these series often generate conflicting estimates. Only by pulling together data into one coherent consistent framework can the statistical agency solve the problem of 'multiple' stories. This can be done by developing a set of Productivity Accounts that are part of an integrated system of National Accounts
Keywords: Productivity accounting -- Canada; Kanada